Surgical Menopause and Frailty Risk in Community‐Dwelling Older Women: Study of Osteoporotic Fractures. Issue 11 (24th September 2018) - Huang, Grace; Coviello, Andrea; LaValley, Michael P.; Ensrud, Kristine E.; Cauley, Jane A.; Cawthon, Peggy M.; Fredman, Lisa
Abstract : Objectives: To determine whether women with surgical menopause have a higher risk of frailty than naturally menopausal women. Design: Prospective cohort study with up to 18 years of follow‐up. Setting: Four U.S clinical centers. Participants: Community‐dwelling white women aged 65 and older (mean 71.2±5.2) enrolled in the Study of Osteoporotic Fractures (N=7, 699). Measurements: Surgical menopause was based on participant self‐report of having undergone bilateral oophorectomy before menopause. The outcome was incident frailty, classified as robust, prefrail, frail, or death at 4 follow‐up interviews, conducted 6 to 18 years after baseline. Information on baseline serum total testosterone concentrations was available for 541 participants. Results: At baseline, 12.6% reported surgical menopause. Over the follow‐up period, 22.0% died, and 10.1% were classified as frail, 39.7% as prefrail, and 28.3% as robust. Surgically menopausal women had significantly lower total serum testosterone levels (13.2 ± 7.8 ng/dL) than naturally menopausal women (21.7 ± 14.8 ng/dL) (p=0.000), although they were not at greater risk of frailty (adjusted odds ratio (aOR)=0.94, 95% confidence interval (CI)=0.72–1.22), prefrailty (aOR=0.96, 95% CI=0.80–1.10), or death (aOR=1.17, 95% CI=0.97–1.42) after adjusting for age, body mass index, and number of instrumental activity of daily living impairments. There was no evidence that oral estrogen use modified these associations. Conclusion: In postmenopausal women, surgical menopause was not associated with greater risk for frailty than natural menopause, even in the absence of estrogen therapy. Future prospective studies are needed to investigate hormonal mechanisms involved in development of frailty in older postmenopausal women.J Am Geriatr Soc 66:2172–2177, 2018.